Identifying strength and weakness of sustainable higher educational assessment approaches - Saadatian, Omidreza; Dola, Kamariah; Salleh, Elias @ Ilias; Mohd Tahir, Osman (Center for Promoting Ideas, 2011)
Sustainable Higher Education (SHE) is regarded as one of the most influential medium of facilitating sustainable development movement in the world. SHE assessment approaches are tools or frameworks which assesses the level of sustainability in higher educational institutions. There have not been any comprehensive studies related to the existing sustainable assessment approaches. It is a relevant issue which merits a proper study to evaluate both the strengths and weakness of those SHE assessment approaches. Archival research technique, content analyses as well as interview were utilized to address this objective. Archival research technique was employed to facilitate the investigation of documents and textual materials in the realm of SHE assessment approach from 12 years starting from 1998. Content analyses were utilized as the research technique which quantify and analyzes the meanings and relationships of concepts and finally interview was employed to validate those two techniques. Comprehensiveness, popularity, novelty, conforming Three Bottom Line (TBL) theory and avoiding Subjective Judgment were the main criteria of evaluation. The study has identified 18 popular SHE assessment approaches out of which Sustainability Tracking and Assessment Rating System (STARS) and Campus Sustainability Assessment Framework (CSAF) were found out to have more strength in comparison of other SHE assessment approaches. The finding can be used for the higher educational institutions which aim to assess the level of SHE in their institutions.